MODEL DAN PRINSIP-PRINSIP PENERJEMAHAN IDIOM DAN GAYA BAHASA DARI BAHASA INGGRIS KE BAHASA INDONESIA - Rudi Hartono (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2012)
Translating idioms and figurative languages is more difficult than translating ordinary expressions. Novel translators usually have problems in translating those aspects because they should reproduce in the target language (TL) the closest natural equivalence of the source language (ST) message, firstly in terms of meaning and secondly in terms of style accepted socio-culturally. Idioms and figurative languages are sometimes not translated into the acceptable ones in the target language. The readers are often confused on what they are reading because expressions are not understandable. The solution of those problems is to provide a model of translating idioms and figurative languages. The model that is designed here to produce high quality of translation product is Tripartite Cycle Model.